2019
DOI: 10.1063/1.5116911
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state vibrations, lifetimes, and nonradiative dynamics of jet-cooled 1-ethylcytosine

Abstract: The S1 excited-state lifetime of jet-cooled 1-ethylcytosine (1ECyt) is ∼1 ns, one of the longest lifetimes for cytosine derivatives to date. Here, we analyze its S0 → S1 vibronic spectrum using two-color resonant two-photon ionization and UV/UV holeburning spectroscopy. Compared to cytosine and 1-methylcytosine, the S0 → S1 spectrum of 1ECyt shows a progression in the out-of-plane “butterfly” mode ν1′, identified by spin-component scaled-second-order coupled-cluster method ab initio calculations. We also repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Nanosecond laser two-color resonant two-photon ionization (2C-R2PI) spectra of the amino-keto tautomers of (a) 6-methylCyt, (b) 1-ethylCyt, , (c) Cyt (with atom numbering), (d) 1-methylCyt, , (e) 5-methylCyt, (f) 5-fluoroCyt, (g) 5,6-trimethyleneCyt, and (g) 1-methyl-5,6-trimethyleneCyt. Ionization wavelength: 226 nm for panels c and e, 223 nm for panel d, 220 nm for panels a and b, and 245 nm for panels f–h.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nanosecond laser two-color resonant two-photon ionization (2C-R2PI) spectra of the amino-keto tautomers of (a) 6-methylCyt, (b) 1-ethylCyt, , (c) Cyt (with atom numbering), (d) 1-methylCyt, , (e) 5-methylCyt, (f) 5-fluoroCyt, (g) 5,6-trimethyleneCyt, and (g) 1-methyl-5,6-trimethyleneCyt. Ionization wavelength: 226 nm for panels c and e, 223 nm for panel d, 220 nm for panels a and b, and 245 nm for panels f–h.…”
mentioning
confidence: 99%
“…Figure shows the 2C-R2PI spectra of the eight cytosines of our set. The spectra of 6-methylCyt and 1M-TMCyt in Figure a,h are reported for the first time, and the previously published spectra ,,, are included for completeness. The S 0 → S 1 spectra all exhibit vibronic progressions in the low-wavenumber “butterfly” and “boat” vibrational modes of the cytosine chromophore, reflecting the out-of-plane framework deformations that occur upon optical excitation of the S 1 ( 1 ππ *) state. , The spectra of 6-methylCyt, Cyt, 1-methylCyt, and 1-ethylCyt break off at low E exc = 250–550 cm –1 , as marked by vertical red arrows in Figure .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fastest decay component (τ 1 ) is present in transients measured at all λ pump 's and exhibits a robust time constant of about 0.25 ps. Because it has been shown that the excited-state deactivation rates of Cy derivatives are very sensitive to the excess energy above the origin, [9,12,[15][16][17]26] this rather independence of the τ 1 component on λ pump over a large energy range ($0.7 eV) suggests that it is not likely to be due to an excited-state population decay of 5mCy tautomers. Indeed, its time scale suggests that it is more likely to be due to an initial intramolecular vibrational-energy redistribution (IVR) occurring in excited 5mCy tautomers.…”
Section: The Assignmentsmentioning
confidence: 99%
“…[3][4][5][6] Among all nucleobases, cytosine (Cy) and its derivatives are probably the most studied system experimentally in the gas phase. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Ultrafast excited-state dynamics of Cy in the gas phase has been explored by several groups. [22][23][24][25][26] Our group has previously used femtosecond pump-probe photoionization spectroscopy to investigate the ultrafast excited-state dynamics of Cy and its microsolvated complexes.…”
Section: Introductionmentioning
confidence: 99%